Thermodynamics of Complex Formation of Transition Metal Ions with Schiff bases in Mixed Solvent Media - Naikwade, S.D.; Mane, P.S.; Chondhekar, T.K. (Asian Journal of Chemistry, 2010)
A series of Schiff bases derived from 2-hydroxy-5-methyl acetophenone and p-toluidine, p-anisidine and p-phenetidine have been synthesized. Their chelating tendencies towards Cu(II), Ni(II), Co(II), Mn(II), Zn(II) and Cd(II) metal ions have been investigated potentiometrically at various temperatures in 50 : 50 ethanol-water medium and 0.1 M (NaCIO4) ionic strength. Thermodynamic parameters for metal-ligand stability constants have been determined by temperature coefficient method.